Studi tentang Pencobaan Bidang Keuangan Fenomena Pinjaman Online di Kalangan Pemuda Remaja - Kalalo Glory Injil Victory Eudia; Maria Benedicta Dian Savitri (LPPM STT Baptis Kalvari, 2023)
As time goes by, advances in technology and finance have made it easier for people to make financial transactions, including accessing online lending services. The increase in the use of social media has also contributed to the rise of consumerism in society, including among Christians. As a result, there has been an increase in the use of online loan services. The relationship between temptation in James 1:14 and the ease of access to financial services in a highly advanced society like today’s is interesting to further investigate. This research is a qualitative descriptive study using a theological approach. The phenomenon of online lending has infiltrated the lives of Christian youth today, and this has led many people to fall into temptation. Some of them follow their own personal desires to meet their own consumerism level. However, every temptation has a purpose to test human faith. This test improves and strengthens the faith that already exists in believers, resulting in the wholeness of divine character during the sanctification process in their lives.